Economic Development and Sustainable Human Resources by Supply Chain Managament in Government Towards in West Kalimantan Indonesia - Martoyo Martoyo; Elyta Elyta; Herlan Herlan; Arifin Arifin (International Journal of Supply Chain Management, 2020)
Abstract- The growth of global supply chains has changed the distribution of incomes across countries. Participation in these supply chains, initiated by the successful completion of low value-added manufacturing tasks, contributed to industrialisation and high rates of economic growth in several Asian developing economies. The quality of economic development and sustainable human resources in government can be seen from excellent service for the realization of a mental revolution. These qualities are demonstrated through the attitude of government officials who are friendly, polite, and a work ethic that is disciplined, productive, and innovative. But the service in Sungai Ambawang Kuala Village, West Kalimantan Indonesia, was allegedly not yet excellent. For this reason, the purpose of this study is to analyze excellent service leading to a mental revolution in the apparatus of Sungai Ambawang Kuala Village through a descriptive qualitative method. Data was collected through observations on the quality of services carried out by the apparatus in Sungai Ambawang Kuala Village, interviews with village heads, village secretaries, heads of government affairs, hamlet heads, and community leaders, and by collecting documents related to services in Sungai Ambawang Kuala Village. Based on research, it is known that until the end of 2016 the village profile as a village development planning document has not been realized and does not yet have clear service standards. It was found that the quality of service of the apparatus of Sungai Ambawang Kuala Village was fulfilled in the aspect of guarantee, real, empathy, and responsiveness but it was still lacking in the aspect of reliability. The conclusion of this study, to overcome the lack of service of government apparatus in serving the community, the concept of service apparatus is harmonized with the vision of a mental revolution that emphasizes the work ethic and the spirit of mutual cooperation. The recommendation given is the existence of a synergistic social movement between the government and the community in routine activities starting from the scope of the family, school to the community.